The Relationship between Physical Activity and Anxiety and Depression Symptoms among Undergraduate Students During the Covid-19 Pandemic in Malaysia - Mun, Sam Jeng; Ee-Vern, Yvern Ng (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2021)
The COVID-19 outbreak has affected many major life structures among Malaysians. Studies have shown that the depressive and anxiety states of university students have been increased due to the differing changes in their daily functioning that are linked to the pandemic. Physical activity as one of the behavioral techniques in Cognitive Behavior Therapy has been known to be able to alleviate common mental disorders which are the symptoms of mild to moderate levels of anxiety and depression. The study examined the relationship between physical activity and the level of anxiety and depression symptoms among undergraduate students in Malaysia during the COVID-19 pandemic. The crosssectional study employed a correlational research design. The study recruited 203 Malaysian undergraduate students who study in Malaysia. The International Physical Activity Questionnaire (IPAQ) and General Health Questionnaire (GHQ-12) were administered to the students through an online platform. Data analysis using the Pearson's Correlation Coefficient showed that there is a significant negative relationship between physical activity and the level of anxiety and depression (p<0.05). The study indicated that physical activity is one of the important strategies to be practiced to improve the mental health condition among undergraduate students. Recommendations to further study other behavioral activation strategies are crucial in improving the mental health of the students.
Keywords: Anxiety, COVID-19, Depression, Mental Health, Physical Activity